Kepemimpinan Kiai dalam Peningkatan Kualitas Pendidikan di Pondok Pesantren Hudaya Diwek Jombang - Burhanudin, Mahfudz; Syamsul Falah, Moh. (Southeast Asian Journal of Islamic Education Management, 2025)
The kiai (Islamic boarding school) is the primary leader of an Islamic boarding school, possessing full authority over the management and development of the institution. The kiai's leadership is a central factor in improving the quality of education, from curriculum management, teaching staff performance, student development, and strengthening the learning system. This study aims to analyze the kiai's leadership model in improving the quality of education at the Hudaya Diwek Islamic Boarding School in Jombang and assess its impact on learning quality. This study employed a descriptive qualitative approach, with data collection techniques including participant observation, in-depth interviews, and institutional documentation. Data were analyzed through three stages: data reduction, presentation, and conclusion drawing. Their validity was tested using source and method triangulation. The results indicate that KH. Agus Achmad Syaikhu's leadership combines charismatic, transformational, and participatory styles effectively to drive improvements in educational quality. Improvements are evident in quantitative indicators, such as a 41.6% increase in student participation in the Musyawarah Kubro (Cultural Consultative Meeting), a 66.6% increase in memorization of the Imrithy (The Book of Imrithy), and a 150% increase in memorization of Al-Fiyyah Ibn Malik. Qualitatively, significant changes have occurred in the students' character, marked by increased activeness, self-confidence, and involvement in Islamic boarding school scientific activities. The novelty of this research lies in its integrative analysis based on quantitative and qualitative indicators, a practice rarely employed in similar studies. This research provides a practical contribution to the development of Islamic education management based on kiai leadership and serves as a reference for other Islamic boarding schools in improving the quality of their education.